2015
DOI: 10.1016/j.amepre.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Post-Cessation Weight Concerns Among Women Calling a State Tobacco Quitline

Abstract: State quitlines should consider tailoring promotional efforts and treatment protocols to include concerns about weight gain, especially for obese African American and Hispanic smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
0
19
1
Order By: Relevance
“…However, the ORs were not statistically significant. Thus, although previous studies showed that anxiety pertaining to weight gain after smoking cessation was higher in overweight or obese smokers13,23,24, the current findings suggest that normal weight smokers are more likely to have a smoking cessation plan.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…However, the ORs were not statistically significant. Thus, although previous studies showed that anxiety pertaining to weight gain after smoking cessation was higher in overweight or obese smokers13,23,24, the current findings suggest that normal weight smokers are more likely to have a smoking cessation plan.…”
Section: Discussioncontrasting
confidence: 85%
“…Smoking is a considerably greater health risk than that associated with weight gain. Nonetheless, weight gain after cessation cannot be ignored12, particularly given concerns related to weight gain that may interfere with smoking cessation 2,10,13,14…”
Section: Introductionmentioning
confidence: 99%
“…The majority of female smokers are concerned about post-cessation weight gain (Beebe & Bush, 2015; Jeffery, Hennrikus, Lando, Murray, & Liu, 2000; Pirie, Murray, & Luepker, 1991; Pomerleau, Zucker, & Stewart, 2001), with 75% reporting that they are unwilling to gain more than 5 lb, and 90% unwilling to gain more than 10 lb (Levine et al, 2001; Pomerleau & Kurth, 1996). In other studies, smokers were asked whether they would relapse if they gained weight up to 20 lb.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of women who quit smoking gain 8 to 10 lb on average [9][10][11][12][13]. Many women smokers report concerns about weight gain as a barrier to quitting [14][15][16][17][18][19][20][21][22][23][24][25], and women quitters who return to smoking identify weight gain as a reason for their relapse [26][27][28][29]. Women who are highly concerned about their weight are more likely to smoke as a means to control their weight [15,30,31].…”
Section: Introductionmentioning
confidence: 99%